Adaptation of the Knowledge about Childhood Autism among Health Workers (KCAHW) Questionnaire: Turkish version - SAVE, DİLŞAD; KARAVUŞ, MELDA; AY, NADİYE PINAR; LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN (KARE PUBL, 2019)
OBJECTIVE: Many checklists and scales have been developed to diagnose the autism spectrum disorder in childhood. However, self-applied questionnaires/scales that can be filled out by health professionals for assessing their knowledge and consciousness of this disorder are still limited. The Knowledge about Childhood Autism among Health Workers self-administered survey was developed by Bakare et al. in 2008. This survey was recruited by many study groups in developing countries. In these countries, knowledge regarding childhood autism is inadequate within community healthcare professionals. METHODS: In our study, the agreed-upon Turkish version of the questionnaire was distributed to the 61 primary care physicians working in Maltepe District of Istanbul Province for the adaptation and validation. RESULTS: The internal consistency coefficient (Kuder-Richarson coefficient of reliability-KR20) of the measurements attained from the Turkish version of the questionnaire was 0.70. The split-half reliability analysis demonstrated that the Guttman Split-half value was 0.84. According to the principal factor analysis of the tetrachoric correlation matrix, the three factors with the highest Eigenvalues were associated with (i) Relatively easy clinical observations, (ii) the signs which require a longer observation time and detailed anamnesis, and (iii) the signs, which require detailed examination and observation. The factors explained cumulatively 65.98% of the total variance. CONCLUTION: The findings obtained in this study showed that the adapted questionnaire addressed in the scope of this study is a valid measure for Turkish society.
Keywords: Awareness; childhood autism; physicians; primary care; validity; DIAGNOSTIC OBSERVATION SCHEDULE; SPECTRUM DISORDER; YOUNG-CHILDREN; IDENTIFICATION; COMMUNICATION; MANAGEMENT; CHECKLIST; VALIDITY